Love them in the life and theology of D.L. Moody - Gundry, Stanley N. 1937- (Chicago, IL Moody, 1999)
Includes bibliographical references and indexes.
Keywords: Moody, Dwight Lyman, -- 1837-1899, -- evangelist; Evangelism -- biography